Women Entrepreneurship and Innovations: A Critical Analysis - Dwibedi, Lalan (Academic Voices: A Multidisciplinary Journal, 2016)
Increased female entrepreneurial activity heralds a progress for women’s rights and optimization of their economic and social living index. Women entrepreneurship is synonymous with women empowerment. Parallel to the male counterparts, female entrepreneurs are catalytic in job creation, innovation and more than tangible contribution to the GNP of the country. An economy thrives when women get a level playing field as men. Innovation works as a catalyst or an instrument for entrepreneurship. Despite all the social hurdles stand tall from the rest of the crowd and are applauded for their achievements in their respective field. The transformation of social fabric of the society, in terms of increased educational status of women and varied aspirations for better living, necessitated a change in the life style of women. This paper endeavors to explore studies related to women entrepreneurship and innovation and how it leads to success and growth of an enterprise.A Academic Voices Vol.5 2015: 16-21